2010
DOI: 10.3109/17435390.2010.507316
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and alterations in expression of DNA damage responsive genes induced by TiO2nanoparticles in human hepatoma HepG2 cells

Abstract: We investigated the genotoxic responses to two types of TiO2 nanoparticles (<25 nm anatase: TiO(2)-An, and <100 nm rutile: TiO2-Ru) in human hepatoma HepG2 cells. Under the applied exposure conditions the particles were agglomerated or aggregated with the size of agglomerates and aggregates in the micrometer range, and were not cytotoxic. TiO2-An, but not TiO2-Ru, caused a persistent increase in DNA strand breaks (comet assay) and oxidized purines (Fpg-comet). TiO2-An was a stronger inducer of intracellular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(129 citation statements)
references
References 69 publications
3
121
1
1
Order By: Relevance
“…TiO 2 has been shown to induce the formation of reactive oxygen species (ROS) in cells (Xue et al, 2010), which can lead to changes in gene expression in response to stress. TiO 2 has also been shown to physically damage DNA (breaking strands and oxidizing purines) and upregulate stress response gene expression as a consequence of ROS generation (Petković et al, 2011). These TiO 2 -induced changes to the cell will have downstream effects on the RAPD patterns generated and are considered genotoxic (causing alteration to genomic DNA integrity, which could lead to cell death or carcinogenesis).…”
Section: Resultsmentioning
confidence: 99%
“…TiO 2 has been shown to induce the formation of reactive oxygen species (ROS) in cells (Xue et al, 2010), which can lead to changes in gene expression in response to stress. TiO 2 has also been shown to physically damage DNA (breaking strands and oxidizing purines) and upregulate stress response gene expression as a consequence of ROS generation (Petković et al, 2011). These TiO 2 -induced changes to the cell will have downstream effects on the RAPD patterns generated and are considered genotoxic (causing alteration to genomic DNA integrity, which could lead to cell death or carcinogenesis).…”
Section: Resultsmentioning
confidence: 99%
“…IMR-90 cells were more sensitive to TNP, showing genotoxicity (ROS-induced DNA adduct formation) [98]. In HepG2 cells, DNA breakage and oxidized purines were found, accompanied by activation of p53 and its downstream DNA damage response genes [99]. Mice given drinking water containing TNPs for five days experienced the formation of 8-hydroxy-2 -deoxyguanosine, ␥-H2AX foci, micronuclei, DNA deletions, and DNA double-strand breaks [100].…”
Section: Toxicity Of Tnps To Mammalian Cellsmentioning
confidence: 99%
“…Any reduction in mitochondrial membrane potential can lead to decreased energy production, which may results cytochrome c release and induce cellular apoptosis via calciumsensitive proteases, or through the activation of caspases and DNA fragmentation enzymes (Calcineurin et al 2001). Several studies in different cell lines showed that TiO 2 NP could cause genotoxicity represented by DNA damage and chromosomal aberrations (Rahman et al 2002;Kang et al 2008;Xu et al 2009;Petković et al 2011). The exposure of peripheral human lymphocytes to TiO 2 NPs can lead to the activation of DNA damage check points and accumulation of tumour suppressor protein p53 (Kang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of peripheral human lymphocytes to TiO 2 NPs can lead to the activation of DNA damage check points and accumulation of tumour suppressor protein p53 (Kang et al 2008). In vitro and in vivo studies of different experimental models showed that nanoTiO 2 could cause genotoxic effects through indirect mechanisms like oxidative stress and inflammation (Driscoll et al 1997;Xu et al 2008;Trouiller et al 2009;Petković et al 2011). ROS are important signalling molecules that can affect cell proliferation, inflammation and cell death (Sha et al 2013).…”
Section: Discussionmentioning
confidence: 99%